Association of rs11209032 and rs1004819 Polymorphisms in Interleukin-23 Receptor Gene With Ankylosing Spondylitis - Müjgan ÖZDEMİR ERDOĞAN,; Tuğba Şule ÇANKAYA,; Alper Murat ULAŞLI,; Saliha Handan YILDIZ,; Evrim Suna ARIKAN TERZİ,; Tuba ÇAVDAR,; Ümit DÜNDAR,; Mustafa SOLAK, (Archives of Rheumatology, 2016)
Objectives: This study aims to investigate the distribution of human leukocyte antigen B27 (HLA-B27) alleles (+/-) and interleukin-23 receptor (IL-23R) gene rs11209032 and rs1004819 polymorphisms among ankylosing spondylitis (AS) patients in a Turkish cohort. Patients and methods: The study sample comprised 106 AS patients (89 males, 18 females; mean age 38.9±10 years; range 19 to 65 years) and 82 healthy controls (70 males, 12 females; mean age 32.15±7.07 years; range 19 to 51 years). Distribution of HLA-B27 alleles (+)/(-) in AS patients were observed by reverse hybridization technique. Genotyping of IL-23R rs11209032 and rs1004819 polymorphisms of AS patients and healthy controls were performed by real time polymerase chain reaction. Results: Of the AS patients, 69 (65.1%) were HLA-B27 positive. Distribution of rs11209032 genotype frequencies in AS group were 31.1% for GG, 50.9% for GA, and 17.9% for AA; while in control group, it was 34.1% for GG, 53.7% for GA, and 12.2% for AA. Distribution of rs1004819 genotype frequencies in AS group were 30.2% for CC, 52.8% for CT, and 17.0% for TT; while in control group, it was 42.7% for CC, 46.3% for CT, and 11.0% for TT. There was no significant difference between AS patients and controls in terms of genotype frequencies of IL-23R gene rs11209032 and rs1004819 polymorphisms. Conclusion: No association was found between AS and IL23R rs11209032 and rs1004819 polymorphisms in this Turkish AS cohort.